FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KESEJAHTERAAN KARYAWAN STUDI KASUS PT. PERKEBUNAN SAWIT KUD MINANGA OGAN - jihan jihan; Septianita Septianita (JASEP, 2022)
This study aims to analyze what factors affect the welfare of employees at PT. Oil palm plantation of KUD Minanga Ogan. This research method uses the case study method. Sampling method using purposive sampling method. Methods of data analysis using Gini ratio and multiple linear regression analysis. Taking the employee population amounted to 30 employees. The results of the research conducted can be concluded that the welfare of employees at PT. KUD Minanga Ogan's oil palm plantations are still relatively low with the number of employees who still have low welfare reaching 22 employees from the 30 employee population sampled. The results of this study indicate that family responsibilities, length of work and salary have a significant effect on the welfare of employees at PT. Oil palm plantation of KUD Minanga Ogan.Keyword: employee, level, Palm, Welfare